Clinical impact of hospital distance and center transfers on adherence and outcomes in familial adenomatous polyposis: A multicenter retrospective study in a defined region of Japan - Kyota Tatsuta; Mayu Sakata; Moriya Iwaizumi; Kazuya Okamoto; Shigeto Yoshii; Yutaro Asaba; Takashi Harada; Kiyotaka Kurachi; Mikihiro Shimizu; Hiroya Takeuchi (PLoS ONE, 2026)
This study aimed to evaluate how hospital distance and changes in surveillance hospitals influence adherence to surveillance, the cumulative risk of familial adenomatous polyposis-related tumors, and survival outcomes in patients with familial adenomatous polyposis. We conducted a multicenter retrospective study in a specific region of Japan and analyzed 79 patients with familial adenomatous polyposis who underwent total colectomy or proctocolectomy between 1987 and 2025 across 9 accredited hospitals. We examined the associations between straight-line distance to the hospital, changes in surveillance centers, and surveillance adherence, as well as the cumulative risk of familial adenomatous polyposis-related tumors and survival outcomes. The 10-year surveillance adherence rate was 86.5%. During follow-up, 31.6% of patients changed hospitals. Hospital distance did not differ significantly between those who maintained or dropped out of surveillance. However, patients residing ≥40 km from their hospital were significantly more likely to switch hospitals (61.5% vs. 13.2%, p < 0.001). Importantly, changes in surveillance hospitals showed no significant association with the cumulative risk of familial adenomatous polyposis-related tumors or survival outcomes. Surveillance dropout occurred in 7.6% of patients. No specific clinical predictors of surveillance dropout were identified; the most common reason for surveillance dropout was patients’ self-assessed low risk following negative screening results. This multicenter study found that hospital distance or changes in surveillance hospitals did not significantly affect adherence to surveillance or clinical outcomes in patients with familial adenomatous polyposis.